Процена метода анализе и интерференције коагулационих анализатора СИСМЕКС ЦН-6000 и СТАГО СТА-Р - orhan, seren; işbilen, Elif (Journal of Medical Biochemistry, 2025)
Abstract Objective: The aim of this study was to compare the analytical methods of STAGO STA-R and SYSMEX CN-6000 coagulation analyzers. Also, to evaluate the effects of lipemia and hemolysis interferences on the methods. STA-R detects clotting using an electromechanical method, while the CN-6000 detects clotting using an optical method. We compared the activated partial thromboplastin time (APTT), prothrombin time (PT), Fibrinogen (FBG) and D-Dimer results of both analyzers. We also examined the effects of hemolysis and lipemia on PT (INR), APTT and FBG analyses. Methods: Randomly selected blood samples from Gaziantep University Hospital patients were used. PT (INR), APTT, FBG, D-Dimer analysis was performed using both analyzers. Precision, comparability and interference studies were performed in the study. Studies were performed according to CLSI documents (H21-A5, EP15-A3, EP07-Ed3) Results: In the precision study, all % CV values were within the acceptable limits of between-subject biologic variation criteria for hemostasis tests. The correlation coefficients of PT (INR), APTT, FBG, D-Dimer results between the two devices were found to be r=0.982 (p<0,01) ,r=0.872 (p<0,01), r=0.945 (p<0,01) and r=0.981 (p<0,01) respectively. In the hemolysis and lipemia interference study, the results were within the limits recommended by Fraser. Discussion: Differences between results in the study may be due to differences in the reagents and methods used. Interferences for both analyzers were assessed to be within the targets recommended by Fraser, but the CN-6000 was found to be unable to perform on highly lipemic samples. Keywords: Blood Coagulation Tests, Hemolysis, Lipemia, Interference, SYSMEX CN-6000, STAGO STA-R.